Celebrando nossos corpos, encrespando nossos fios : a transição capilar como política de visibilidade em narrativas autobiográficas de mulheres negras - Arantes, Dariane Lima (2019)
In this research, we articulate the dynamics between communication and consumer cultures in the debate centered on the social visibilities from the mediatic experiences of black women. It is interesting to see how the identity and cultural flows that emerge from these mediated autobiographical experiences interact with social realities and cultural contexts, linked to subjectivities, symbolic and imaginary disputes, in a context permeated by a whitening logic and the myth of racial democracy. Starting from reflections on biographical space, our discussion turns to the capillary transition narratives of four figures from different media spheres: the actress Taís Araújo, the entrepreneur Alexandra Loras, the singer Ludmilla and the youtuber Rayza Nicácio. . As a problematic of this study, we ask if aesthetics can act as a possibility of negotiation of meanings, starting from the understanding that from the experience of capillary transition emerge senses linked to black bodies, which encompass stigmas and exclusions, but also possible meanings of (re)signification and (re)existence.